A Research About the Reading Habit Readiness Situations of Preschool Children: Hacettepe University Beytepe Preschool Sample - Tolga Çakmak; Bülent Yılmaz (Türk Kütüphaneciliği)
Reading habit is generally gained in childhood and especially in primary school years. Although this capability is gained in primary school years, it is seen that there are some factors that affect gaining reading habit in preschool period. These factors are family, environment and preschool institutions. This study enables an insight about effects of these factors on gaining reading habit of preschool children. It also emphasizes some research results that are obtained from Hacettepe University Beytepe Preschool (HÜBA). Data are collected from peer to peer questionnaire studies with 50 children at the age of six which is the closest group to the primary school. Within the scope of the research, information is also enabled from observations of environment and structured interview with preschool educators about reading habit readiness activities of Hacettepe University Beytepe Preschool. Finally, results that are elaborated from the analyses are evaluated within the framework of the factors that have some effects on preschool children’s obtainment of reading habit and reading readiness. According to evaluations, it was seen that families have a major role on creating reading environment and providing reading readiness of children. Besides families; friends, environmental factors and instructors are other important elements for children’s reading readiness situations.